Transparency promoted by process mining: an exploratory study in a public health product management process - Neubauer, Thais Rodrigues; Araujo, Renata Mendes de; Fantinato, Marcelo; Peres, Sarajane Marques (Anais do Latin American Symposium on Digital Government (LASDiGov), 2022)
Public transparency enables the exercise of democracy by the active participation of citizens in the public management. Even though promoting transparency is an essential conduct in a democratic context, its practice is still incipient. In this context, process mining emerges as an agent to promote public transparency as the data related to public processes event logs may have the potential to enable visual and analytical analysis of the process execution. In order to exemplify how process mining might promote public transparency, we present a study considering the health products' management process of a health surveillance agency. Our analysis reveals details about the process execution logic as well as the actions that impact the efficiency of its management.